The role of intestinal translocation of E.coli in the development of acute obstructive pyelonephritis in an experiment - Yerzhan Sharapatov; Yermek Turgunov; Alyona Lavrinenko (National Scientific Medical Center, 2023)
Aim: To study the role of E. coli intestinal translocation in the development of acute obstructive pyelonephritis in an experiment. Material and methods: An experimental study was conducted on 60 male rabbits weighing 3000±500 g. The animals were divided into 3 groups of 20 animals each: experimental, control and intermediate control group. The acute obstructive pyelonephritis with the ureter blocking by laparotomy and introduction of the strain into the intestine were simulated in the animals of the experimental group. In the control group, the model was performed anologically as in the experimental group, but without the ureter blocking. In the intermediate control group, laparotomy was performed, the ureter was isolated without blocking and without the introduction of a bacterial strain. 10 animals of each group were removed from the experiment on the 3rd and 5th days, kidney tissue and urine were intake. As a reference marker strain, the laboratory strain E. coli No. 49579 was used, which was obtained from a patient with a urological infection and had resistance to cefepime, ciprofloxacin and tetracycline. Biomaterials were studied by microbiological examination and subspecific typing of strains using the MALDI-TOF MS method, antibiotic sensitivity was determined. Results: E. coli strain was isolated in all animals of the experimental group and in 2 animals of the control group on the 5th day. During subspecific typing by the MALDI-TOF MS method, the isolated strains were identical in ribosomal proteins, and also had the same sensitivity to the said antibiotics. When analyzing the amount of lg CFU E.coli in urine after the experiment between the experimental and control group, we found that, on day 3, there were statistically significant differences between the groups (p=0.005), and on day 5, the amount of lg CFU E.coli was 13 times greater (p=0.004).A comparative analysis of the lg CFU E.coli index in kidney tissue on 3 (p=0.004) and 5 (p=0.003) days revealed statistically significant differences between the experimental group and the control group. Conclusion: The results of identification and subspecific typing of isolated microorganisms confirmed that the strains isolated from the urinary tract were identical to the reference strain introduced into the gastrointestinal tract during the experiment, which confirms the role of translocation of intestinal microorganisms in the development of acute obstructive pyelonephritis.